EXTH-74. IND-ENABLING CHARACTERIZATION OF DUAL DRD2- AND ClpP-TARGETING AGENT ONC206 AS THE NEXT IMIPRIDONE FOR CLINICAL NEURO-ONCOLOGY. (9th November 2020) - Prabhu, Varun; Morrow, Sara; Kawakibi, Abed Rahman; Jitkova, Yulia; Jung, Jinkyu; Madhukar, Neel; Garnett, Mathew; McDermott, Ultan; Benes, Cyril; Wechsler-Reya, Robert; Elemento, Olivier; DeMorrow, Sharon; et al.
Abstract: ONC201 is the first bitopic antagonist of dopamine receptor D2 (DRD2) and allosteric mitochondrial protease ClpP agonist, that is well tolerated and induces durable tumor regressions in H3 K27M-mutant glioma patients. ONC206, a derivative of ONC201, is also a bitopic DRD2 antagonist that exhibits enhanced non-competitive effects, nanomolar potency, and disruption of DRD2 homodimers. In these studies, a FITC-casein degradation assay revealed that ONC206 also acts as an agonist of human ClpP and has a 3-fold improved potency. GEPIA database analysis showed ClpP mRNA was overexpressed in glioblastoma cells relative to normal cells. Broad nanomolar efficacy of ONC206 (GI50 < 78-889nM, 72h) was observed in >1, 000 GDSC cancer cell lines with the highest sensitivity in cell lines exhibiting high ClpP and/or DRD2+/DRD5- RNA expression signatures. Among solid tumors, nervous system related cell lines were particularly sensitive. ONC206 reduced the viability of normal human fibroblasts at higher doses (GI50 > 5µM), suggesting a wide therapeutic window. Antitumor efficacy without body weight loss was observed with 50 mg/kg weekly oral ONC206 in a subcutaneous xenograft model of DRD2-overexpressing, dopamine-secreting tumor cells. Oral ONC206 at 50mg/kg exhibited a ~12 µM plasma Cmax and ~6 hours terminal half-life in Sprague-Dawley rats. Additionally, 5–10 fold higher ONC206 concentrations were observed in adrenal gland, bile duct, brain and bone marrow relative to plasma. GLP toxicology studies with weekly oral ONC206 in Sprague-Dawley rats and beagle dogs revealed no dose-limiting toxicities. Mild and reversible body weight changes were observed at the highest evaluated dose in both species. The no-observed-adverse-effect level was ≥ 16.7 mg/kg in dogs and ≥ 50 mg/kg in rats that exceed efficacious doses. A 50 mg starting dose of ONC206 was selected for the first-in-human open label, dose escalation, and food effect Phase I study in biomarker-enriched adult recurrent primary CNS tumors.